Seaweed-associated microbes as a novel source of crop agrochemicals - Susan McKenna; Everton Henrique Da Silva Pereira; Antoine Fort (Frontiers in Marine Science)
The climate crisis necessitates new and expanded agrochemical options to address the challenges in current agricultural production. The marine flora represents an attractive source of novel bioactives compounds with potential relevance to agriculture (including both crops and livestock applications), human health, and biomaterials. While significant research is currently underway focusing on discovering and characterising bioactives derived directly from algal biomass, an often-overlooked aspect of seaweeds - or marine macro-organisms in general - is their close association with a diverse array of microorganisms, forming what is now referred to as holobiont systems. As such, the marine flora hosts a variety of microbes, including epiphytic and endophytic bacteria and fungi. This reservoir of microbial biodiversity itself offers a promising, yet largely untapped, source of novel bioactives with potential applications in the agriculture and healthcare industries. This mini-review aims to discuss the recent findings in the bioactivities of the Seaweed-Associated Microbiome (SAM) and specifically explore the potential applications of seaweed microbiome-derived bioactives as a novel source of agrochemicals relevant to crop growth, health, and pest management.